Evolution and Functional Diversity of GATA Transcription Factors in Filamentous Fungi: Structural Characteristics, Metabolic Regulation and Environmental Response - Danni Hu; Ruoyu Zhao; Yingxu Lin; Chunmiao Jiang (Microbiology Research)
Filamentous fungi hold critical industrial value for their ability to produce enzymes, antibiotics, organic acids, and food fermentation. GATA transcription factors (TFs) serve as central regulators of nitrogen metabolism, synthesis of secondary metabolites, stress adaptation, and directly influence fungal development and pathogenicity in filamentous fungi. In this review, we primarily discuss the structural characterization, different types, and phylogenetic analysis of filamentous fungi GATA TFs in filamentous fungi. Subsequently, we systematically summarize the multifunctions of GATA TFs in the mycelial growth, morphological differentiation, and conidial development of filamentous fungi. In addition, we explore their functions in the synthesis of secondary metabolites such as antibiotics (e.g., cephalosporins, penicillins) and organic acids (e.g., ganoderic acid, fumaric acid) in filamentous fungi. Furthermore, we focus on the key roles of GATA TFs AreA and AreB in nitrogen and carbon metabolism in filamentous fungi and their potential synergistic regulatory relationships. Finally, we review the important roles of GATA TFs in the adaptation of filamentous fungi to environmental changes. This review provides research ideas for the development of genetically engineered strains with optimized growth characteristics, increased target metabolites in the fermentation production process, and enhanced environmental adaptability.